“No Way Out Except From External Intervention”: First-Hand Accounts of Autistic Inertia - Buckle, Karen Leneh; Leadbitter, Kathy; Poliakoff, Ellen; Gowen, Emma (Frontiers in Psychology, 2021)
This study, called for by autistic people and led by an autistic researcher, is the first to explore ‘autistic inertia’, a widespread and often debilitating difficulty acting on their intentions. Previous research has considered initiation only in the context of social interaction or experimental conditions. This study is unique in considering difficulty initiating tasks of any type in real life settings, and by gathering qualitative data directly from autistic people. Four face-to-face and 2 online (text) focus groups were conducted with 32 autistic adults (19 female, 8 male, 5 other), aged 23-64 who were able to express their internal experiences in words. They articulate in detail the actions they have difficulty with, what makes it easier or harder to act, and the impact on their lives. Thematic analysis of the transcripts found four overarching themes: descriptions of inertia, scaffolding to support action, the influence of wellbeing, and the impact on day-to-day activities. Participants described difficulty starting, stopping and changing activities that was not within their conscious control. While difficulty with planning was common, a subset of participants described a profound impairment in initiating even simple actions more suggestive of a movement disorder. Prompting and compatible activity in the environment promoted action, while mental health difficulties and stress exacerbated difficulties. Inertia had pervasive effects on participants’ day-to-day activities and wellbeing. This overdue research opens the door to many areas of further investigation to better understand autistic inertia and effective support strategies.